Corn Yield Response to Plant Populations - D. E. Shoup; E. A. Adee; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
Corn hybrid development with a focus on drought tolerance has emerged in recent years, and producers have questions about their yield performance across a range of plant populations. A two-year study was conducted to determine the yield of corn hybrids across several plant populations. Corn hybrids responded differently in 2013 and 2014. In 2013, a lower yield environment occurred. The hybrid with drought tolerance had the greatest yield of 95 bu/a at a plant population of 21,500 plants/a, whereas the non-drought-tolerant hybrid’s greatest yield was 90 bu/a at a plant population of 13,500 plants/a. In 2014, the yield environment was significantly higher. The hybrid with drought tolerance had the greatest yield of 174 bu/a at the greatest plant population of 35,500 plants/a, and the non-drought tolerant hybrid’s greatest yield was 169 bu/a at a plant population of 29,500 plant/a.
Keywords: corn plant populations; drought tolerance